2021
DOI: 10.1021/acs.jpca.1c03517
|View full text |Cite
|
Sign up to set email alerts
|

Product Detection of the CH(X2Π) Radical Reaction with Cyclopentadiene: A Novel Route to Benzene

Abstract: The reaction of the methylidyne radical (CH(X 2 Π)) with cyclopentadiene (c-C 5 H 6 ) is studied in the gas phase at 4 Torr and 373 K using a multiplexed photoionization mass spectrometer. Under multiple collision conditions, the dominant product channel observed is the formation of C 6 H 6 + H. Fitting the photoionization spectrum using reference spectra allows for isomeric resolution of C 6 H 6 isomers, where benzene is the largest contributor with a relative branching fraction of 90 (±5)%. Several other C 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 90 publications
(180 reference statements)
0
20
0
Order By: Relevance
“…As Caster et al concluded in their work [14], the CH cycloaddition, driven by strong attractive potential between the reactants, is likely to dominate over insertion or abstraction mechanisms at room temperature. In addition, recent product detection experiments coupled with computational studies [18] suggest that cycloaddition is likely to account for up to 90% of the overall mechanism. Therefore, we have chosen as a test processes on which to show the applicability of our methodology on open‐shell systems, only the cycloaddition reaction between the CH (X 2 Π) radical and cyclopentadiene.…”
Section: Resultsmentioning
confidence: 99%
“…As Caster et al concluded in their work [14], the CH cycloaddition, driven by strong attractive potential between the reactants, is likely to dominate over insertion or abstraction mechanisms at room temperature. In addition, recent product detection experiments coupled with computational studies [18] suggest that cycloaddition is likely to account for up to 90% of the overall mechanism. Therefore, we have chosen as a test processes on which to show the applicability of our methodology on open‐shell systems, only the cycloaddition reaction between the CH (X 2 Π) radical and cyclopentadiene.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple data sets using a 248 nm photolysis laser with cyclopentadiene and without OH radical precursors were collected at 373 K in a previous study. 47 Argon or krypton (for hν < 7.9 eV) are used in a gas filter to absorb harmonics of the undulator radiation. For data recorded below 8.0 eV with argon in the gas filter, a MgF 2 window is placed in the path of the ionizing radiation to suppress harmonics of the undulator fundamental photon energy.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology has been described in detail by Glowacki et al 61 and has been employed to investigate OH radical reactions with unsaturated hydrocarbons 60 as well as CH radical reaction with ammonia 62 and cyclopentadiene. 47 Isomerization and decomposition unimolecular rates of the reaction intermediates along the PES were calculated using Rice−Ramsperger−Kassel−Marcus (RRKM) theory. Energy transfer processes were modeled using a constant average energy transferred, ΔE down .…”
Section: Master Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Additionally, expansion of a five-membered ring to a sixmembered ring has been demonstrated through the reaction of pyrrole with the methylidyne radical (CH) to form pyridine 51 and the reaction of cyclopentadiene with CH to form benzene (Figure 1c). 52,53 CH in its ground state has been detected in combustion environments, 54−56 in the interstellar medium, 57,58 and under plasma conditions. 59 Reactions between CH and small unsaturated hydrocarbons and carbonyls can result in CH insertion to a π-bond through a cyclic intermediate (cycloaddition) followed by ring-opening.…”
Section: ■ Introductionmentioning
confidence: 99%